Event-driven spectrotemporal feature extraction and classification using a silicon cochlea model - Xu, Ying; Perera, Samalika; Bethi, Yeshwanth; Afshar, Saeed; van Schaik, André (Frontiers in Neuroscience, 2023)
This paper presents a reconfigurable digital implementation of an event-based binaural cochlear system on a Field Programmable Gate Array (FPGA). It consists of a pair of the Cascade of Asymmetric Resonators with Fast Acting Compression (CAR FAC) cochlea models and leaky integrate and fire (LIF) neurons. Additionally, we propose an event-driven SpectroTemporal Receptive Field (STRF) Feature Extraction using Adaptive Selection Thresholds (FEAST). It is tested on the TIDIGTIS benchmark and compared with current event-based auditory signal processing approaches and neural networks.